A Dual-band Magnetoelectric Dipole Antenna by Microstrip Line - Zhang, Hao (International Journal of Mechanical and Electrical Engineering, 2024)
This paper proposes a dual-band magnetoelectric dipole antenna. By changing the size of the electric dipole and the magnetic dipole in the traditional magnetoelectric dipole, the two resonant frequencies are moved to high and low frequencies respectively, so as to realize the dual-band characteristics of the magnetoelectric dipole antenna. Finally, the two impedance bandwidths are measured to be 14.94% (1.6-1.86GHz) and 11.01% (4.25-4.74GHz), and the average gains are 9.8dBi and 6.3dBi respectively.